Area-Wide Management of Fruit Fly Pests. - Perez-Staples, Diana. (Taylor & Francis Group, 2019)
This book supplies the latest research on the biology, management procedures, and control strategies of fruit flies of economic importance. It considers an integrative approach covering topics including behavior, genetics, biological control, integrated pest management, host-plant interactions, trap design, and transgenics of fruit flies.